Análise das correlações entre narrativa, estética, música e estereoscopia, em Divertida Mente - Granatto, Danilo César (2018)
The following project has as its main purpose to analyse a series of elements that compose the cinematic language applied to the 3D animation Inside Out (Pete Docter, Walt Disney Pictures; Pixar Animation Studios. 2015) and explore the correlations and the interdependency amongst them. Selecting this movie as the object of this study has multiple advantages, as it is a current piece and was conceived by two of the most respected animation studios, being a proper model to compare with the present scenario. Firstly, the historical facts about the subject are presented, flowing through the technological evolution and the development of methods that assist the processes of creating animations until the present day. Subsequently, it is necessary to measure the values of the oscillations and variations of data in each of the elements capable of analysis according to the duration of the movie; with the objective to explore the creation process of colors, musical compositions and the stereoscopy showcased in the movie. Parallel to that, all the results from all the diagrams created will be approached, and all of its respective components and their contributions to potencialize the dramaturgy convenient in certain parts of the plot, with the theoretical background on the layers of narrative structure from The Writer's Journey, by Cristopher Vogler. Finally, the results previously mentioned will be compared amongst each other, showcasing the behavior of these elements and their contributions as stimulators of the dramatic tension.